A FINITE ELEMENT ANALYSIS OF CRITICAL BUCKLING LOAD OF COMPOSITE PLATE AFTER LOW VELOCITY IMPACT - Ramadhan, Redha Akbar; Suada, M. Giri; Syamsudin, Hendri (Indonesian Journal of Aerospace, 2020)
Composite is a material formed from two or more materials that macroscopically alloyed into one material. Nowadays, composite has been generally applied as lightweight structure of aircraft. This is due to the fact that composites having high strength-to-weight ratio. It means the composites have the capability to take on various loads, despite their lightweight property. Laminate composite is one type of composite that has been generally used in aircraft industries. This type of composite is susceptible to low-velocity impact induced damage. This type of damage can be happening in manufacture, operation, or even in maintenance. Low-velocity impact could cause delamination. Delamination happens when the plies of laminated composites separated at the interface of the plies. This type of damage is categorized as barely visible damage, means that the damage couldn’t be detected with visual inspection. Special method and tool would be needed to detect the damage. Delamination will decrease the strength of the laminated composite. Delamination can be predicted with numerical simulation analysis. With increasing capability of computer, it is possible to predict the delamination and buckling of laminated composite plate. This research presents the comparisons of buckling analysis results on laminated plate composite and damaged laminated plate composite. By the result of LVI simulation, it is shown that low velocity impact of 19.3 Joule causing 6398 mm2 C-Scan delamination area inside the laminated composite. The delamination causing structural instability that will affect buckling resistance of the plate. The result of analysis shows that the existence of delamination inside laminate composite will lower its critical buckling load up to 90% of undamaged laminate’s critical buckling load.